Green Logistics Role in Enhancing Green Supply Chain Performance Through Green Procurement and Eco-Friendly Transportation - Paula Olivia Lokman; Timotius FCW Sutrisno (SAFE-Network, 2026)
This study aims to analyze the influence of green procurement and eco-friendly transportation on green supply chain performance in manufacturing companies in East Java with green logistics as a mediating variable. The approach used is a quantitative explanatory approach with a Likert scale questionnaire survey of 1–7 to 143 managers and supervisors involved in supply chain management and operations. Then the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that green procurement and eco-friendly transportation have a positive and significant effect on green logistics, while green logistics and green procurement have a positive and significant effect on green supply chain performance. However, the direct effect of eco-friendly transportation on green supply chain performance was not proven to be significant. These findings also indicate that green logistics significantly mediates the effect of green procurement and eco-friendly transportation on green supply chain performance, thus confirming the role of green logistics as a key capability that translates green practices upstream into improved environmental and operational performance along the supply chain.